Analisis Kritis Penggunaan Strict Liability Dalam Berbagai Peraturan Perundang-Undangan Di Indonesia - Muh Farhan Arfandy; Ranggalawe Suryasaladin (Indonesian Journal of Criminal Law, 2023)
The formulation of the problems of this research are: 1. What is the Urgency of Strict Liability in Enforcement of Environmental Law in Indonesia? and; 2. What are the Efforts to Implement Strict Liability in Environmental Disputes in Indonesia? The research method used is a normative method using a conceptual approach and a statutory approach. The conclusions from this study are 1. By using Strict Liability, the constraints experienced by sufferers of environmental impacts can be minimized. Then another thing that can be considered as something that benefits the victim is that the polluter has been held responsible, regardless of whether he is guilty or not. and; 2. The removal of the phrase "without the need to prove an element of guilt," by Law No. 11 of 2020 Concerning Job Creation does not make Article 88 UUPPLH where Strict Liability is removed. Regarding the concern that the formulation of Strict Liability in the Ciptaker Law will further obscure the understanding of Strict Liability.